Global report on food crises 2018 - Russo, Luca (2018)
Luca Russo SPECIAL EVENT Washington, DC Launch--2018 Global Report on Food Crises: From Humanitarian to Developmental Responses Co-Organized by IFPRI and Food Security Information Network (FSIN) APR 27, 2018 - 09:30 AM TO 11:00 AM EDT